Neurotoxicity in young adults 20 years after childhood exposure to lead: the Bunker Hill experience. Issue 8 (August 1998) - Stokes, L; Letz, R; Gerr, F; Kolczak, M; McNeill, F E; Chettle, D R; Kaye, W E
Abstract : OBJECTIVES: An epidemiological study of young adults was conducted to determine whether environmental exposure to lead during childhood was associated with current adverse neurobehavioural effects. METHODS: The exposed group consisted of 281 young adults who had been exposed environmentally to lead as children and the unexposed referent group consisted of 287 age and sex frequency matched subjects. Information on demographics, past and current health, and past exposures to neurotoxicants, and responses to the Swedish Q16 questionnaire were collected by interview. Standard neurobehavioural and neurophysiological tests were administered by computer or trained technicians. K x ray fluorescence was used to estimate tibial bone lead concentrations among the exposed and unexposed groups. Associations were examined between the exposed group and referents and tibial bone lead concentration and the neurobehavioural and neurophysiological outcomes of interest. RESULTS: Among the measures of peripheral nerve function, after controlling for confounders, sural sensory nerve evoked response amplitude, peroneal motor nerve compound motor action potential amplitude, vibrotactile thresholds of fingers and toes, and standing steadiness were significantly associated with exposure group. Among the neurobehavioural tests, hand-eye coordination, simple reaction time latency, trails B latency, symbol digit latency, serial digit, and learning error score were also significantly associated with exposure group after controlling for confounders. Exposed subjects had significantly more neuropsychiatric symptoms than the referents. Associations between tibial bone lead concentration and scores for vocabulary, vibrotactile thresholds of the fingers, and vibrotactile thresholds of the toes approached significance. CONCLUSIONS: Significant adverse central and peripheral neurological effects were found in a group of young adults 20 years after childhood environmental exposure to lead when compared with non-exposed controls. The absence of a significant association between neurological outcomes and tibial bone lead concentration, and the presence of significant associations between neurological outcomes and exposure group may be due to either the magnitude of measurement uncertainty in K x ray films relative to the actual tibial bone lead concentration in these young non-occupationally exposed subjects, or uncontrolled confounding of the exposure group.